Rural Roads and Local Market Development in Vietnam - Mu, Ren; van de Walle, Dominique (2012)
We assess impacts of rural road rehabilitation on market development at the commune level in rural Vietnam and examine the geographic, community, and household covariates of impact. Double difference and matching methods are used to address sources of selection bias in identifying impacts. The results point to significant average impacts on the development of local markets. There is also evidence of considerable impact heterogeneity, with a tendency for poorer communes to have higher impacts due to lower levels of initial market development. Yet, some poor areas are also saddled with other attributes that reduce those impacts.